Susceptibility of Jordanian tomato landraces to tomato yellow leaf curl virus - Qaryouti, M.M.=700 1 Hurani, O.M.; Mahadeen, A.Y.
(En, Fr, Es)
ilus., 11 ref.
Keywords: VIRUS; BEMISIA TABACI; LYCOPERSICON ESCULENTUM; GEMINIVIRUS RIZADO AMARILLO TOMATE; ITALIA